Influence of fruit maturity, maceration length, and Ethanol amount on chemical and sensory properties of Merlot wines - Casassa, Luis Federico; Beaver, Christopher W.; Mireles, María S.; Larsen, Richard C.; Hopfer, Helene; Heymann, Hildegarde; Harbertson, James F. (2018)
Selected winemaking conditions were applied to fruit with ~20.3 and ~24.9 Brix over two seasons. Merlot grapes were harvested 33 (2011) and 34 (2012) days apart. At each harvest, half of the must was adjusted to emulate the other harvest’s soluble solids content to evaluate the effect of ethanol (EtOH) on phenolic extraction at different fruit maturities. Additionally, two maceration lengths of 10 days (control) and 30 days (extended maceration; EM) were tested. Control wines had significantly higher anthocyanin content, saturation, and red color component, whereas EM wines had enhanced tannin extraction from seeds, lower anthocyanin content, lower saturation, higher hue, and higher large polymeric pigment content. EtOH differences up to 2.7% (v/v) showed no significant effect on tannin and anthocyanin extraction, suggesting a minor role of this solvent under standard winemaking conditions. The later harvest date had a prevailing and positive effect on the sensory profile of the wines over winemaking factors such as maceration length and EtOH treatments. Wines from the early harvest fruit were defined by fresh vegetal character, acidity, and low color saturation. Wines from the late harvest fruit were defined by viscous mouthfeel, sweet taste, and fruit-derived aromas. Extended maceration shifted the sensory profile toward higher astringency, lighter and yellower color components, and cooked vegetal aromas. Chaptalization of early harvest fruit to 25 Brix shifted the sensory profile from cooked and fresh vegetable characters toward sweet taste, alcoholic, floral, chocolate/caramel attributes, astringency, and viscous mouthfeel. Overall, unripe fruit and the application of extended maceration had a negative impact on the sensory profile of the wines, whereas chaptalization of unripe fruit yielded wines with an improved sensory profile.